DATA PROCESSING AND STORAGE SYSTEM FOR RECORDS OF WAVE DISTURBANCES IN THE ATMOSPHERE DUE TO VOLCANIC ERUPTIONS - Firstov P.P.; Filippov Yu.A. (My University, 1997)
A data processing and storage system for records of wave disturbances in the atmosphere generated by volcanic eruptions is described. The system was developed using acoustic signals recorded during eruptions of Kamchatkan volcanoes during the last 30 years. The system consists of three units: 1) preprocessing of original observations, 2) data base, and 3) data processing software. Digitized acoustic signals (AS) were obtained for eleven volcanoes using different types of their eruptive behavior. The amount of digitized information was 0.8 Gb by the end of 1996. About 30% of the data base consists of the acoustic signals generated by one of the most active volcanoes of the work, Klyuchevskoi, during its Strombolian-type eruptions. Unique AS records were digitized for a lateral blast of Shiveluch volcano that occurred on November 12, 1964. The data base management system was Paradox for Windows 5.0 used with a Quattro Pro electronic table. The MEZOZAVR, SPP, STADIA, and SeisGram programs were used to process the digitized signals. Examples of data processing are presented.